Progress and recent novelties of Ingeniería e Investigación Journal - Pavas, Andres (Ingeniería e Investigación, 2017)
In previous editorial letters, data regarding the Journal positioning, visibility and management have been presented. Regarding positioning in citational databases, in Pavas (2015), a comparison among the results in databases like Scimago Journal Rank (SJR), Journal Citation Report (JCR), and Google Scholar (GS) is shown. In Pavas (2016a), the h5 index of the Colombian engineering journals is highlighted. In terms of the journal’s visibility, in Pavas (2016b), indicators up to December 2016 are presented. The editorial team of Ingeniería e Investigación Journal (I&I for their initials in Spanish) wants to share with the authors and readers some of their recent results.